(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
In this paper, we analyze the theatrical performance O Machucado de Magnólia, published on the Barbixas YouTube channel, highlighting how the actors construct the male and female identities of their characters through the dynamics of improvisational theater. We rely particularly on the foundations of improv theater, based on Moscheto and Achatkin; on the tension between mental and perceptual imagery promoted by this form of theater, in dialogue with Bergson, Mitchell, Contrera & Hattori; on the relationship between fiction and non-fiction as discussed by Aranha and Pesavento; and on the notion of Performative Acts by Butler, supported by Louro and Saffioti.